PREFERÊNCIA DE CORTE DE Acromyrmex crassispinus (FOREL, 1909) E Acromyrmex ambiguus (EMERY, 1887) (HYMENOPTERA: FORMICIDAE) POR DIFERENTES ESPÉCIES DE EUCALIPTOS EM LABORATÓRIO - João Luis Osório Rosado (Ciência Florestal, 2014)
The search for new leafcutter ant management and control methods have been the aim of several studies over the country, propelled by economic and environmental aspects. The establishment of resistant or less preferred species for the cut can contribute substantially in this subject. This way, the objective of this study was to evaluate the cutting preference between the species Corymbia citriodora, Eucalyptus benthamii, Eucalyptus camaldulensis, Eucalyptus dunnii, Eucalyptus globulus and híbrido de Eucalyptus urophylla XEucalyptus grandis by Acromyrmex ambiguus and Acromyrmex crassispinus in laboratory. Therefore, leafs were offered simultaneously to six colonies of each species in bioassays with chance to choose. However, in the tests without chance to choose, only the least preferred species in the previous test were utilized. For Acromyrmex crassispinus, the species Eucalyptus camaldulensis and híbrido de Eucalyptus urophylla X Eucalyptus grandis were the most cutted, besides Corymbia citriodora, Eucalyptus dunni and Eucalyptus globules were less preferred. Acromyrmex ambiguus showed similar preference pattern, adding Eucalyptus benthamii among the most preferred one and excluding Eucalyptus dunnii from the least preferred.